The Impact of Nanoparticulate Drug Delivery Systems on Cancer Therapy and the Role of Artificial Intelligence - Dash, Santosh Kumar; Padhan, Ashutosh; Khan, Abdul Sayeed; Behera, Tusara Kanta; Mohapatra, Sachhidananda; Parta, Sulagna; Sahoo, Ranjan Kumar (International Journal of Pharmaceutical Investigation, 2026)
Cancer remains a leading cause of global mortality. Conventional treatments such as chemotherapy, radiation, and surgery often lead to severe side effects and limited effectiveness. Nanoparticulate Drug Delivery Systems (NDDS) offer novel strategies to enhance drug targeting, solubility, and treatment outcomes. This review discusses the types, mechanisms, advantages, challenges, and future directions of NDDS in cancer therapy. The role of Artificial Intelligence (AI) in optimizing drug formulations, targeting strategies, and real-time monitoring is also explored. NDDS improve drug solubility, circulation time, and targeted delivery while minimizing side effects. Mechanisms such as the Enhanced Permeability and Retention (EPR) effect, active targeting, and controlled release enhance therapeutic efficacy. AI assists in drug design, nanoparticle characterization, personalized therapy, and resistance prediction. NDDS, supported by AI-driven approaches, have significant potential to revolutionize cancer treatment. Addressing biocompatibility, scalability, regulatory hurdles, and tumor heterogeneity remains essential for wider clinical adoption.
Keywords: Cancer; Nanoparticulate Drug Delivery System; Artificial intelligence